Microwave assisted carbon nanofibers for removal of zinc and copper from waste water - Mujawar, Mubarak; Faghihzadeh, A.; Tan, K.; Sahu, J.; Abdullah, E.; Jayakumar, N. (American Scientific Publishers, 2017)
Copyright © 2017 American Scientific Publishers All rights reserved.Removal of toxic metals is one of the biggest challenges in ensuring safe water for all as well as protecting the environment. To reduce environmental problems, the carbon nanofibers (CNFs) are the most promising candidates for the adsorption of heavy metals. CNFs have been successfully synthesized by microwave heating technique and improved to be an outstanding adsorbent for the removal of heavy metal from waste water. A comparative study of the adsorption capacity of carbon CNFs in removal of Zn2+ and Cu2+ was investigated. Statistical analysis revealed that the optimum conditions for the highest removal of Zn2+ and Cu2+ are at pH 9.5 and 6, adsorbent dosage 100 and 50 mg, agitation speed of 150 and 100 rpm and adsorption time for both 20 minutes respectively. The removal efficiency of Zn2+ and Cu2+ for an initial concentration of 2 mg/L was 94.5% 98.8% respectively. The maximum adsorption capacities (qm) of 1.049 and 1.07 mg/g for CNFs were obtained to remove Zn2+ and Cu2+ respectively. The adsorption isotherms are well described by both Langmuir and Freundlich models and adsorption kinetic obeyed pseudo-second order. Hence, CNFs are the most promising candidate for removal of heavy metal from wastewater treatment and separation process.